SUATU TINJAUAN YURIDIS ALAT BUKTI PENGAKUAN DALAM PENYELESAIAN PERKARA PERDATA DALAM PERBUATAN MELAWAN HUKUM - Mareni Mareni (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractGeneral arrangements concerning the burden of proof in the settlement of a civil case are essentially contained in the provisions of Article 163 HIR / 283 Rbg, which states: Whoever says has a right, or specifies an event to affirm his right, or denied the rights of others, then the person must prove his or her right or the event.The development of jurisprudence shows, among other things, that recognition as a proof does not always have perfect evidentiary power. Therefore, to assess the strength of the proof is left to the judge's wisdom. This means that the role of acknowledgment as evidence in civil procedure law is highly dependent on their case.This means that the law needs to tighten the rules of civil procedure law with the development of the community who want it because in civil procedure law, not only seek the formal truth merely, but must always try to find and find the material truth.